IFRS vs. Japanese GAAP Tested with Value Relevance Methodology - Williams, Zachary (The Indonesian Journal of Accounting Research, 2024)
This study is one of the first empirical evaluations of voluntary IFRS adoption in Japan, and it shows that the earnings announcements of Nikkei 225 firms using IFRS have higher value relevance than earnings announcements of Nikkei 225 firms using Japanese GAAP (earning announcements from 2008-2022). This study uses value relevance methodology that relates surprise earnings (calculated with Bloomberg-compiled analyst earnings expectations) to abnormal returns over the 12 months before the announcement, a methodology evolved from the seminal work of Ball and Brown (1968). Another finding here is the strength of qualitative variables to measure surprise earnings. Japan represents a unique opportunity to compare IFRS to a local standard in a large, developed economy using similar companies except for the accounting standard. These results provide essential data to the IFRS literature, stakeholders navigating the Japanese accounting environment, and other jurisdictions weighing the benefits of IFRS.